Tingkat Partisipasi Masyarakat dalam Perencanaan Pembangunan di Desa Pali Kecamatan Bittuang Kabupaten Tana Toraja - Claudia Indriani; Sulaiman Asang; Amril Hans (Development Policy and Management Review (DPMR), 2021)
In general, this study aims to determine how the level of community participation in development planning in Lembang Pali, Bittuang District. By looking at how the community is involved in every implementation of the development plan deliberation. The basis of this research is a quantitative approach with descriptive quantitative research type. The technique used in data collection is a question naire method and studying data related to research.